Characterization of Phenolic Acids Profile from Chilean Red Wines by High-Performance Liquid Chromatography - Cotoras-Tadic, M; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Aguirre-Quintana, M; Aguirre-Quintana, M; Mendoza-Espinola, L; Mendoza-Espinola, L (Sociedad Chilena de Quimica, 2011)
The success of Chilean wine in the international market has led to an important attention on the development of science and technology for wine differentiation, productivity, and quality. In order to report the profile of phenolic acid compounds in Chilean red wines, an SPE technique over ODS column was used followed by a reverse phase HPLC program that was developed to separate, characterize and quantify six phenolic acids (caffeic, gallic, p-coumaric, protocatechuic, syringic and vanillic acids) in four red Chilean wines varieties (Cabernet Sauvignon, Carménère, Merlot and Syrah) from grapes cultivated in the central zone of Chile. The separation was carried out on an RP C-18 column using a binary gradient elution and diode array detection.